Single-fed broadband CP bidirectional antenna with double-layer diagonally aligned plates for universal UHF-RFID applications - Dentri, Sitthichai; Pookkapund, Khanet; Luadang, Bancha; Akkaraekthalin, Prayoot; Phongcharoenpanich, Chuwong (My University, 2020)
This research proposes a single-fed broadband circularly polarized (CP) bidirectional antenna operable in 840-960 MHz frequency band for readers of universal UHF-RFID applications. The proposed antenna is comprised of upper-layer conductor, lower-layer conductor, and wall patches. The upper-layer conductor consists of two diagonally aligned rectangular copper plates with a feeding gap at the center, and the lower-layer conductor is of two diagonally adjoined rectangular plates. The upper- and lower-layer conductors are adjoined with the wall patches. The diagonal alignment technique of the upper- and lower-layer plates was used to realize circular polarization and improve 3-dB axial ratio (AR) bandwidth. The double layers were deployed to improve impedance bandwidth (|S11| < -10 dB) and achieve bidirectional radiation pattern. The simulated impedance bandwidth and 3-dB AR bandwidth were 772.19-1014.6 MHz (27.13%) and 675-1000 MHz (38.80%), and the corresponding measured results were 759-1011 MHz (28.47%) and 648-1110 MHz (52.55%). The simulated LHCP/RHCP half-power beamwidth (HPBW), 3-dB AR beamwidth, and gain were 56° - 90°/54° - 92°, 60° - 104°, and 4.94 - 5.89 dBic, while the corresponding measured results were 52° - 98°/62° - 97°, 96° - 126°, and 4.28 - 5.72 dBic. As a result, the single-fed broadband CP bidirectional antenna is applicable to universal UHF-RFID readers. Besides, the novelty of this research lies in the use of diagonal alignment of conducting plates to achieve circular polarization and wider AR bandwidth.